The spindle pole body component Spc98p interacts with the γ‐tubulin-like Tub4p of Saccharomyces cerevisiae at the sites of microtubule attachment - Geißler, Silke; Pereira, Gislene; Knop, Michael; Schiebel, Elmar (The EMBO journal, 1996)
Tub4p is a novel tubulin found in Saccharomyces cerevisiae. It most resembles gamma-tubulin and, like it, is localized to the yeast microtubule organizing centre, the spindle pole body (SPB). In this paper we report the identification of SPC98 as a dosage-dependent suppressor of the conditional lethal tub4-1 allele. SPC98 encodes an SPB component of 98 kDa which is identical to the previously described 90 kDa SPB protein. Strong overexpression of SPC98 is toxic, causing cells to arrest with a large bud, defective microtubule structures, undivided nucleus and replicated DNA. The toxicity of SPC98 overexpression was relieved by co-overexpression of TUB4. Further evidence for an interaction between Tub4p and Spc98p came from the synthetic toxicity of tub4-1 and spc98-1 alleles, the dosage-dependent suppression of spc98-4 by TUB4, the binding of Tub4p to Spc98p in the two-hybrid system and the co-immunoprecipitation of Tub4p and Spc98p. In addition, Spc98-1p is defective in its interaction with Tub4p in the two-hybrid system. We suggest a model in which Tub4p and Spc98p form a complex involved in microtubule organization by the SPB.
Gesehen am 31.08.2017